Materiality, emotion, and collective memory: The communicative power of memorial architecture - May Phoo Khin (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: This study investigates how the architectural design of the Hiroshima Peace Memorial Museum shapes visitors’ emotional and cognitive engagement with traumatic history. This study investigates how architectural language, materiality, and spatial organization function as non-verbal communicative instruments that shape visitor emotional responses and collective memory in memorial spaces, situating these findings within the broader discourse of city branding and place authenticity to demonstrate that heritage architecture constitutes a strategic urban asset in constructing and projecting authentic cultural identity on the global stage. Methods: Using mixed methods, including analysis of 150 visitor reflections and survey data, the research examines how materiality (raw concrete, glass), spatial sequencing, and multisensory experience influence emotion and memory. Findings: Over 80% of visitors reported profound emotional reactions to the architecture, especially the contrast between dark, narrow corridors and luminous galleries. Raw concrete was seen as a symbol of destruction and resilience, while glass conveyed fragility and hope. Spatial immersion strongly predicted memory retention (r = 0.68, p < .01), emphasizing architecture’s role as an affective and mnemonic medium. NVivo themes like “Emotional Disruption” and “Journey from Darkness to Light” support theories such as Nora’s lieux de mémoire and Pallasmaa’s sensory architecture. Conclusion: Overall, this trauma-responsive, healing-centered model demonstrates how architectural design can foster peacebuilding and remembrance, providing a practical framework for future memorials. Novelty/Originality of this article: This study offers a practical, trauma–responsive architectural framework that can be used as a design model for future memorials.